BELANJA PUBLIK SEKTOR SOSIAL TERHADAP IPM SERTA PDRB DI 38 KABUPATEN/KOTA PROVINSI JAWA TIMUR - Amelia, Rosa; Arisetyawan, Kukuh (Jurnal Ekonomika : INDEPENDEN, 2024)
This study aims to evaluate whether government budget allocations in the education, health, and social protection sectors have an influence on the Human Development Index and economic growth for 38 districts/cities in East Java Province. Using data from 2020, the panel data regression method was used to assess the interrelationship of various variables. The research results indicate that the health and education sectors have positive and significant impacts on the Human Development Index (HDI), which in turns has an impact on economic growth. In contrast, social protection expenditure is not significant to HDI or economic growth. This study confirms the importance of investment in the sectors of health and education in improve people's quality of life and economic productivity. This is proven by strengthening the human capital, which is the pillar of sustainable economic growth. However, for social protection spending, more targeted management is also needed to have a more optimal impact on human and economic development. The research gives insights for policy makers to design government strategies for inclusive and competitive empowerment.